Clinical and genetic profile in index patients with spinocerebellar ataxia type 3 in Indonesia: case report. Issue 7 (July 2021) - Aminah, Siti; Huda, Fathul; Gamayani, Uni; Pusparini, Iin; Mochyadin, Mochammad Faisal Afif; Sribudiani, Yunia; Ibrahim, Norlinah Mohamed; Achmad, Tri Hanggono
Abstract: Spinocerebellar ataxia (SCA) is an autosomal dominant hereditary disease with progressive course, and no causal therapy. Diagnostics are still challenging, due to facility and protocols, and so as in Indonesia. As a national referral center, Dr. Hasan Sadikin Central General Hospital has received a lot of patients from all over Indonesia, particularly from Western Java. Study related to SCA (including clinical and genetic profile) is still limited in Indonesia. We identified index patients from three families with ataxia, hence intend to determine their clinical and genetic pattern. The hereditary pattern is autosomal dominant. Scale for the assessment and rating of ataxia (SARA) shows mild and moderate ataxia. Inventory of non-ataxia signs (INAS) scores of the patients were 3, 5 and 6. Montreal cognitive assessment-Indonesian version (MOCA-INA) shows only one patient has mild cognitive impairment, despite young age. Barthel index shows 1 subject has moderate dependency. Mutation in Ataxin3 polyQ repeats shows pathologically long CAG repeats, 72, 10; 72, 10; and 72, 23 respectively in mutant and wild type allele. We diagnosed the index patients with spinocerebellar ataxia type 3. This study is the first case series study in Indonesia. The hereditary pattern is clearly shown as an autosomal dominant ataxia. The clinical and genetic profile was varied, and the symptom is progressive and deteriorates overtime, including wide based gait, speech problem, motor and sensor complaint, and cognitive decline complaint. Despite the same polyQ stretch length, the onset and clinical characteristics of patients are diverse. Abstract : Autosomal dominant, Familial ataxia, Indonesia, Polyglutamine, Spinocerebellar ataxia.